2022
DOI: 10.1002/edn3.288
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes of genetic structure and diversity in a marine diatom genus discovered via metabarcoding

Abstract: Diatoms’ bloom dynamics, with seasonal cycling of waxes and wanes of cell abundance, imply frequent bottleneck and expansion events that can leave signatures in the genetic structure and diversity of populations. We explored changes in genetic diversity and structure within multiple species of the planktonic marine diatom genus Pseudo‐nitzschia living in sympatry in the Gulf of Naples (Tyrrhenian Sea, Italy) over 48 sampling dates (from 2011 to 2013) by means of metabarcode data. The genus Pseudo‐nitzschia inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 94 publications
0
18
0
Order By: Relevance
“…Lastly, we discuss the potential of rbcL metabarcoding to draw meaningful conclusions about population structure and microevolution. We focused on two widely studied groups, and in the case of Pseudo-nitzschia galaxiae , one species for which speciation hypotheses exist ( Ruggiero et al, 2015 , 2022 ; Turk Dermastia et al, 2022 ). When using metabarcoding as a population genetics tool, caution must be exercised with sequencing technology and ASV calling algorithms, which are not error-prone and therefore can artificially inflate haplotype composition ( Nearing et al, 2018 ; Turon et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we discuss the potential of rbcL metabarcoding to draw meaningful conclusions about population structure and microevolution. We focused on two widely studied groups, and in the case of Pseudo-nitzschia galaxiae , one species for which speciation hypotheses exist ( Ruggiero et al, 2015 , 2022 ; Turk Dermastia et al, 2022 ). When using metabarcoding as a population genetics tool, caution must be exercised with sequencing technology and ASV calling algorithms, which are not error-prone and therefore can artificially inflate haplotype composition ( Nearing et al, 2018 ; Turon et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since its first record in 2004 (as “ Pseudo‐nitzschia new genotype”) in a clone library‐based DNA‐metabarcoding study of the 28S rDNA fragment (McDonald et al, 2007 ), P. allochrona has always been the only species of the group found in summer–autumn, never showing up among the more than 187 strains of the P. delicatissima ‐complex retrieved in winter–spring in the area over more than 10 years, all invariably identified as P. delicatissima , P. arenysensis , or P. dolorosa . Temporal segregation is also confirmed by an annual overview based on 28S rDNA clone library, in which P. allochrona (as P. delicatissima IV) was responsible for the late summer‐early autumn blooms of 2009 and 2010 (Ruggiero et al, 2015 ), while a three‐year HTS study based on 17,763 environmental 18S rDNA‐V4 barcodes has again shown P. allochrona to be abundant in summer in 2011 and 2013 (Ruggiero et al, 2022 ). In all the three above‐mentioned metabarcoding studies, P. arenysensis/P.…”
Section: Discussionmentioning
confidence: 85%
“…was responsible for the late summer-early autumn blooms of 2009 and 2010 (Ruggiero et al, 2015), while a three-year HTS study based on 17,763 environmental 18S rDNA-V4 barcodes has again shown P. allochrona to be abundant in summer in 2011 and 2013 (Ruggiero et al, 2022). In all the three above-mentioned metabarcoding studies, P. arenysensis/P.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations